Notes on the genus Hyalolaena (Apiaceae) with description of a new species H. zhang-minglii from Xinjiang, western China - Lyskov, Dmitry; Kljuykov, Eugene; Ukrainskaja, Uliana; Tojibaev, Komiljon (Phytotaxa, 2019)
Hyalolaena zhang-minglii (Apiaceae) is described and illustrated as a new species from the Eastern Tian Shan, Narat Range, China. The species is related to H. issykkulensis but differs by filiform terminal segments of basal leaves, equal narrow-winged fruit ribs, short root, and greater number of secretory ducts on commissural side of mericarp. Hyalolaena depauperata is synonymized under H. jaxartica. Two species of Hyalolaena, namely H. bupleuroides and H. intermedia, are newly recorded for Uzbekistan.